EVALUASI STRATEGIPT PERTAMINA (PERSERO) DALAM UPAYA MENINGKATKAN COMPETITIVE ADVANTAGE UNIT PERKAPALAN - , Yada Prawira Ganta ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Purpose â The purpose of this paper is to evaluate the companyâs strategy which has done to improve the competitive advantage in accordance to companyâs vision to be a world class shipping company. Research Method - This research use a combination method of qualitative and quantitative. An interview and discussion with companyâs management and also the employee is done as an approach of this research. Some calculation is also done related to the companyâs operational performance. An extensive literature study is done to support the analysis and recommendation to the result of this research. Findings â Internal data related to the companyâs operational performance in the past years and external data related to oil & gas and also shipping industries shown some findings that become a fundamental analysis and recommendation give to the company. Research Limitations â This research has some limitations in providing data, especially internal data related to the financial performance. That limitations can be overcome by doing a deep interview adn discussion with the management. A comprehensif literature study is also done to overcome the limitations. Practical Implications â Company could find out the strategy effectivity which has done till today, understand the companyâs business position related to competition, challenge and opportunities and company could also determine an alternatif strategy to speed up the companyâs performance in accordance to overcome the vision to be a world class shipping company.